2016
DOI: 10.1080/09168451.2016.1165601
|View full text |Cite
|
Sign up to set email alerts
|

Generating hESCs with reduced immunogenicity by disrupting TAP1 or TAPBP

Abstract: Human embryonic stem cells (hESCs) are thought to be a promising resource for cell therapy, while it has to face the major problem of graft immunological rejection. Major histocompatibility complex (MHC) class I expressed on the cell surface is the major cause of graft rejection. Transporter associated with antigen presentation 1 (TAP1) and TAP-associated glycoprotein (TAPBP) play important roles in regulating MHC class I expression. In this study, we generated TAP1- and TAPBP-deficient hESC lines, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Our results show also the downregulation of MAPK9 , encoding for JNK2 protein, the absence of which was associated with the hyperproliferation of the CD8+ T cells [ 57 ]. Moreover, the result is in line with the upregulation of TAPBP , encoding for tapasin protein, required to increase the affinity with MHC class I for the activation of the immunogenicity [ 58 ]. It is noteworthy that our results show that the genes belonging to the pathways that we took into consideration for the immune system are not statistically differentially expressed in frontal and in parietal cortex of MS patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 94%
“…Our results show also the downregulation of MAPK9 , encoding for JNK2 protein, the absence of which was associated with the hyperproliferation of the CD8+ T cells [ 57 ]. Moreover, the result is in line with the upregulation of TAPBP , encoding for tapasin protein, required to increase the affinity with MHC class I for the activation of the immunogenicity [ 58 ]. It is noteworthy that our results show that the genes belonging to the pathways that we took into consideration for the immune system are not statistically differentially expressed in frontal and in parietal cortex of MS patients compared to healthy controls.…”
Section: Discussionmentioning
confidence: 94%
“…Remarkably, Cui et al found that the expression levels of HLA-ABC were upregulated even in the TAPBP knock-out cells by the interferon treatment, and immune rejection was reduced in TAPBP-deficient hESC line. Potent inflammatory molecules such as eicosanoids are able to upregulate TAPBP [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…hPSCs (NIH Codes: WA01, H1) were maintained on irradiated CF1 feeder cells as described in our previous paper ( 20 ). Before lentiviral transduction and hematopoietic differentiation, hPSCs were maintained in chemically defined mTeSR™1 medium (StemCell Technologies, Canada) without feeder as described previously ( 21 ). The 293T cells were maintained in DMEM medium (Invitrogen, USA) supplemented with 10% fetal bovine serum (FBS, Hyclone, USA).…”
Section: Methodsmentioning
confidence: 99%